2014
DOI: 10.1152/ajpregu.00516.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to water immersion in humans: impact on cerebral perfusion

Abstract: Episodic increases in cerebrovascular perfusion and shear stress may have beneficial impacts on endothelial function that improve brain health. We hypothesized that water immersion to the level of the right atrium in humans would increase cerebral perfusion. We continuously measured, in 9 young (means ± SD, 24.6 ± 2.0 yr) healthy men, systemic hemodynamic variables along with blood flows in the common carotid and middle and posterior cerebral arteries during controlled filling and emptying of a water tank to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 40 publications
9
76
1
Order By: Relevance
“…), changes in conduit vessel diameter (Carter et al . b ), and increased arterial compliance (Boussuges, ). As such, we thought a true sham group which underwent chronic thermoneutral water immersion was necessary to isolate the effects of repeated rises in core temperature in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…), changes in conduit vessel diameter (Carter et al . b ), and increased arterial compliance (Boussuges, ). As such, we thought a true sham group which underwent chronic thermoneutral water immersion was necessary to isolate the effects of repeated rises in core temperature in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that an increase in middle cerebral artery blood velocity during water immersion is due to increases in blood pressure (Carter et al. ). However, they used a colder water temperature than we did (~30°C vs. ~35°C), which would likely cause differences in total peripheral resistance between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant increase in PETCO 2 and cerebral perfusion suggests that a link between the two could exist during HOWI (Carter et al. ). However, it is not clear if the rise in cerebral perfusion during HOWI is due to acute hypercapnia or the combined effects of HOWI, including elevated PETCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently this concept has been illustrated via water immersion, where CBF increases in a similar magnitude to that obtained during landbased exercise, 128 and more so when water immersion was combined with exercise. 129 How this then translates to longerterm effects (i.e., after a training intervention) has not yet been reported, but the combined strategy may result in greater improvements in cerebrovascular function than previously reported from a standard land-and aerobic-based training study.…”
Section: Optimizing Cerebrovascular Adaptation Through Brain-targetedmentioning
confidence: 93%